Hybrid Composite of Sn(IV)-Porphyrin and Mesoporous Structure for Enhanced Visible Light Photocatalytic Degradation of Organic Dyes - Nirmal Kumar Shee; Beom-Hyeok Park; Hee-Joon Kim (Molecules, 2023)
Two hybrid composites (SnP@MCM−41 and SnP@SiO2) were fabricated by chemical adsorption of (trans-dihydroxo)(5,10,15,20-tetraphenylporphyrinato)tin(IV) (SnP) on mesoporous structured Mobil Composition of Matter No. 41 (MCM−41) and SiO2 nanoparticles. These materials were characterized by Fourier-transform infrared spectroscopy, ultraviolet–visible spectroscopy, fluorescence spectroscopy, transmission electron microscopy, and field-emission scanning electron microscopy techniques. The incorporation of SnP into MCM−41 and SiO2 supports efficient photocatalytic degradation of the anionic erioglaucine, cationic rhodamine B, and neutral m-cresol purple dyes under visible light irradiation in an aqueous solution. The performances of degradation of these dyes by these photocatalysts under visible light irradiation varied from 87 to 95%. The pseudo-first-order degradation rate constant of organic dyes for SnP@MCM−41 was higher than those of SnP@SiO2 and SnP. These visible light photocatalysts showed remarkable stability and reliable reusability.